A study on the effect of structure and P-doping of Si thin film as an anode for lithium rechargeable batteries - Song, Jin O.; Shim, Heung Taek; Byun, Dong Jin; Lee, Joong Kee (ADVANCES IN NANOMATERIALS AND PROCESSING, PTS 1 AND 2, 2007)
Effects of substrate temperature and phosphor doping on electrochemical characteristics of the silicon film anode were investigated. The silicon thin films were synthesized directly on copper foil by radio-frequency capacitively coupled plasma-enhanced chemical-vapor deposition (r.f.-CVD). The cyclability of the silicon anode greatly depends on the surface morphology and surface resistivity. The silicon film anodes which have granular structure and high conductivity showed higher cyclability than those of planer and low conductivity, respectively.